2020
DOI: 10.1093/eurpub/ckaa195
|View full text |Cite
|
Sign up to set email alerts
|

Brief alcohol intervention at a municipal registry office: reach and retention

Abstract: Background The aim was to investigate the suitability of a municipal registry office for alcohol screening and brief intervention. We analyzed whether trial participation and retention differ by alcohol- and health-related, demographic and socio-economic participant characteristics. Methods Over 3 months, all 18- to 64-year-old visitors of a registry office were systematically screened. Persons with alcohol consumption in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 27 publications
3
10
1
Order By: Relevance
“…None of the sociodemographic variables (age, gender, educational attainment, marital status, living status, having children, having children in household, yearly household income) was significantly associated with willingness to participate. Some studies have found that younger individuals are more prone to participate in alcohol interventions than older individuals (35,36,38). However, we did not find such an association.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…None of the sociodemographic variables (age, gender, educational attainment, marital status, living status, having children, having children in household, yearly household income) was significantly associated with willingness to participate. Some studies have found that younger individuals are more prone to participate in alcohol interventions than older individuals (35,36,38). However, we did not find such an association.…”
Section: Discussioncontrasting
confidence: 99%
“…As such, one may assume that willing and unwilling employees were not systematically different with regard to how much they drank, how they construed drinking in general as well as work-related drinking more specifically, and what effects they expected alcohol to produce. These findings are in line with previous studies that have revealed no systematic differences in terms of intervention participation based on weekly consumption and frequency of heavy episodic drinking (35), overall alcohol use and consequences (36), typical number of drinks per week (38), or blood alcohol concentration (37). We did, however, find that those willing to participate reported less alcohol-related presenteeism, i.e., occurrences of episodes where on-the-job performance have been thwarted by alcohol consumption.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations